Efficacy and Safety of Intravitreal Gene Therapy for Leber Hereditary Optic Neuropathy Treated within 6 Months of Disease Onset - Newman, Nancy J.; Yu-Wai-Man, Patrick; Carelli, Valerio; Moster, Mark L.; Biousse, Valerie; Vignal-Clermont, Catherine; Sergott, Robert C.; Klopstock, Thomas; Sadun, Alfredo A.; Barboni, Piero; DeBusk, Adam A.; Girmens, Jean François; et al. (Ophthalmology (Rochester, Minn.), 2021)
To evaluate the efficacy of a single intravitreal injection of rAAV2/2-ND4 in subjects with visual loss from Leber hereditary optic neuropathy (LHON). RESCUE is a multicenter, randomized, double-masked, sham-controlled, phase 3 clinical trial. Subjects with the m.11778G>A mitochondrial DNA mutation and vision loss ≤6 months from onset in 1 or both eyes were included. Each subject’s right eye was randomly assigned (1:1) to treatment with rAAV2/2-ND4 (single injection of 9 × 1010 viral genomes in 90 μl) or to sham injection. The left eye received the treatment not allocated to the right eye. The primary end point was the difference of the change from baseline in best-corrected visual acuity (BCVA) between rAAV2/2-ND4–treated and sham-treated eyes at week 48. Other outcome measures included contrast sensitivity, Humphrey visual field perimetry, retinal anatomic measures, and quality of life. Follow-up extended to week 96. Efficacy analysis included 38 subjects. Mean age was 36.8 years, and 82% were male. Mean duration of vision loss at time of treatment was 3.6 months and 3.9 months in the rAAV2/2-ND4–treated eyes and sham-treated eyes, respectively. Mean baseline logarithm of the minimum angle of resolution (logMAR) BCVA (standard deviation) was 1.31 (0.52) in rAAV2/2-ND4–treated eyes and 1.26 (0.62) in sham-treated eyes, with a range from −0.20 to 2.51. At week 48, the difference of the change in BCVA from baseline between rAAV2/2-ND4–treated and sham-treated eyes was −0.01 logMAR (P = 0.89); the primary end point of a −0.3 logMAR (15-letter) difference was not met. The mean BCVA for both groups deteriorated over the initial weeks, reaching the worst levels at week 24, followed by a plateau phase until week 48, and then an improvement of +10 and +9 Early Treatment Diabetic Retinopathy Study letters equivalent from the plateau level in the rAAV2/2-ND4–treated and sham-treated eyes, respectively. At 96 weeks after unilateral injection of rAAV2/2-ND4, LHON subjects carrying the m.11778G>A mutation treated within 6 months after vision loss achieved comparable visual outcomes in the injected and uninjected eyes.